Mapping of Nickel Laterite Resources Using Geographical Information Systems (Sig), Case Study Koninis Region, Central Sulawesi Province - Firdaus, F; Bakri, Suriyanto; Arman, Muh. (Journal of Geology and Exploration, 2022)
The Map Banggai geology sheet especially Bunta has ultramafic rocks so it needs to be mapping the laterite nickel resources. This study aims to determine the spread, determine the levels of mineral elements contained and determine the estimated nickel laterite resource in the research area. The research method was carried out by taking field data and testing the sample levels then analyzed using the application of Geographic Information Systems (GIS). The results showed that the distribution of laterite nickel was found in the ultramafic unit area with elevations between 110 - 170 m which extended from north to south of the research area with an area of ​​29.25 ha, levels of Ni elements for Cut Off Grade (COG) were 1.6% and Fe 34.29% with a thickness of 3 m and an estimated nickel laterite (hypothetical) resource of 1,140,750 tons.